Predictors of Parent Stress and Internalizing Symptoms Using the Multidimensional Feeding Questionnaire: An Exploratory Structural Equation Modeling Approach - (:unkn) unknown (My University, 2020)
Pediatric feeding problems (FP) are common behavioral difficulties among typically developing children. Most studies focused on understanding the etiology and impact of pediatric feeding disorders (PFD) in clinical inpatient or outpatient settings. Although studies have documented the impact of PFD on parent stress and internalizing symptoms, these studies did not examine multiple feeding domains (e.g., child mealtime problems, parent feeding strategies, and the parent-child feeding relationship). The current study evaluated the psychometric properties of the Multidimensional Feeding Questionnaire (MFQ) and the association between feeding related variables and parent stress and internalizing symptoms among community parents and children. Results indicated that a 9-factor 48-item MFQ yielded good fit to the data. Increased frequency of Child Avoidant/Distracting Mealtime Behaviors was associated with increased parent stress and internalizing symptoms. Parents with higher scores on Consistent Mealtime Schedule subscale was associated with decreased parent stress and internalizing symptoms. Parents should be screened for mental health concerns during well-child visits. Clinicians should treat both child FP and parent mental health when concerns arise.
Keywords: community sample; exploratory structural equation modeling; internalizing symptoms; parent stress; pediatric feeding disorders; pediatric feeding problem